Study On Gas-Liquid Two-Phase Flow Characteristics of Low Liquid Holding Capacity In Micro-Inclined Pipelines - Wei, Jiayi; Yu, Jingwen; Xue, Wenjing (International Journal of Natural Resources and Environmental Studies, 2025)
With the expansion of oil and gas resource development to complex terrain areas, the problem of gas-liquid two-phase flow in long-distance pipeline transportation of wet natural gas has become a core concern in the industry. This article systematically reviews the research progress on the flow characteristics, critical liquid carrying velocity, pressure drop, and holdup prediction models of gas-liquid two-phase flow in response to the decrease in transportation efficiency and safety risks caused by liquid accumulation in low-lying areas of wet natural gas pipelines. Research has shown that existing achievements have preliminarily revealed the dynamic mechanism of fluid accumulation and airflow carrying, but there is still a lack of systematic research on the non-uniformity of flow in complex terrains, the universality of models for high-pressure conditions with large pipe diameters, and droplet entrainment effects. Domestic and foreign experimental and theoretical models (such as laminar flow model and ARS interface model) provide a basis for parameter prediction, but the limitations of experimental conditions and the closure problem of interface parameters restrict engineering applications. Future research needs to integrate fractal theory, high-speed measurement technology, and deep learning algorithms to construct a cross scale gas-liquid interface dynamic model, strengthen the coupling mechanism of multiple physical processes, and verify actual pipeline data to improve the accuracy of pipeline design and operation optimization. This review provides direction references for theoretical breakthroughs and technological innovations in the safe and efficient transportation of wet natural gas pipelines